ANALISIS KUALITAS PELAYANAN PADA PT LADFANID KONSULTINDO BATAM - Ardani Ramadhon; Welly Sugianto (LPPM Universitas Putera Batam, 2024)
This study is conducted at consulting services. However, not all conculting services can be accepted by customers. The author in this study obtained data from up to 30 customer respondents, then carried out IPA and Servqual calculations. Based on the IPA results, the highest score was providing complete service with a Tki level of 83.33 and the lowest was that the staff scheduled meetings with customers quickly. with Tki 43.88. There are 7 statements in Science Quadrant I, 7 statements in Quadrant II and 3 statements in Quadrant III and 6 statements in Quadrant IV. Based on the results from SERVQUAL, the highest customer satisfaction is in the Emphaty dimension with Q: 0.81 and the smallest is in Responsiveness at 0.43.